Mommy laid an egg : where do babies come from? - Cole, Babette (San Francisco : Chronicle Books, 1993)
Two children explain to their parents, using their own drawings, where babies come from.
Keywords: Sex instruction for children-Juvenile literature; Sex instruction for children; Reproduction